Effects of Ammonium on Assimilate Translocation and Storage Root Growth in Sushu16 in Root-Swelling Stage - Wenjing Yao; Rui Zhou; Qin Tan; Chun Zhuang; Wenqi Shao; Chuan Chen; Chuanzhe Li (Agronomy, 2025)
Ammonium greatly influences nutrient partitioning and root architecture, particularly in the tuberous crops where assimilate translocation is critical for yield formation. However, relatively few studies have systematically delved into the physiological and molecular mechanisms of ammonium on assimilate translocation and root growth in sweetpotato (Ipomoea batatas Lam.). In this study, we investigated the morphological, physiological, and molecular effects of different concentrations of ammonium (0, 0.5, 1.0, 3.0, 5.0 mM) on the growth of the Sushu16 variety in the root-swelling stage. The plant weight and leaf area index of Sushu16 seedlings exhibited a progressive increase with elevated ammonium levels. However, the weight, volume, and number of storage roots (SRs) displayed a trend of a rapid rise and substantial decline, peaking at 1 mM ammonium. Similarly, the chlorophyll content, photosynthetic rate, and stomatal conductance were significantly increased with 1 mM ammonium treatment. Further, the contents of CK, ABA, and IAA increased first and then decreased, reaching a maximum at 1 mM ammonium. Notably, the “down then up” trend of sucrose content in leaves and stems contrasted with the fall–rise pattern of starch content in SRs at 1 mM ammonium. Furthermore, we screened 34 significant DEGs involved in photosynthesis, starch biosynthetic processes, and hormone signal pathway in SRs by RNA-Seq. All the results indicated that 1 mM ammonium had a promotive effect on source–sink conversion and SR production in Sushu16, which highlights potential targets for breeding or agronomic strategies to optimize yield formation in sweetpotato.